2014
DOI: 10.1096/fj.13-246363
|View full text |Cite
|
Sign up to set email alerts
|

Disheveled regulates precoupling of heterotrimeric G proteins to Frizzled 6

Abstract: Frizzleds (FZDs) are classified as G-protein-coupling receptors, but how signals are initiated and specified through heterotrimeric G proteins is unknown. FZD6 regulates convergent extension movements, and its C-terminal Arg511Cys mutation causes nail dysplasia in humans. We investigated the functional relationship between FZD6, Disheveled (DVL), and heterotrimeric G proteins. Live cell imaging combined with fluorescence recovery after photobleaching (FRAP) revealed that inactive human FZD6 precouples to Gαi1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
73
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 63 publications
(98 reference statements)
14
73
2
1
Order By: Relevance
“…FZD 6 exists in an inactive-state complex with heterotrimeric Ga i and Ga q (Kilander et al, 2014b) similar to what was observed for the muscarinic M 3 receptor (Qin et al, 2011). Agonist stimulation of the FZD 6 -G protein complex is followed by rapid dissociation (Kilander et al, 2014b). The FZD isoform, FZD 4 , on which this study focuses has so far not been connected to signaling through heterotrimeric G proteins.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…FZD 6 exists in an inactive-state complex with heterotrimeric Ga i and Ga q (Kilander et al, 2014b) similar to what was observed for the muscarinic M 3 receptor (Qin et al, 2011). Agonist stimulation of the FZD 6 -G protein complex is followed by rapid dissociation (Kilander et al, 2014b). The FZD isoform, FZD 4 , on which this study focuses has so far not been connected to signaling through heterotrimeric G proteins.…”
Section: Introductionsupporting
confidence: 64%
“…In contrast to transmembrane receptors, intracellular proteins, such as the heterotrimeric G proteins, are not directly affected by surface CL in this assay. The mobile fraction of intracellular proteins is reduced only upon interaction with CL-immobilized surface proteins (Qin et al, 2008(Qin et al, , 2011Kilander et al, 2014b). In cells transfected with fluorescently tagged FZD 4 , Ga, and untagged bg, we found that the mobile fraction of FZD 4 was remarkably reduced by surface cross-linking (Fig.…”
Section: Fzdmentioning
confidence: 71%
See 3 more Smart Citations